Peningkatan Pengendalian Kualitas Sebagai Upaya Meminimalkan Produk Cacat pada Kayu Ekspor - Febianti, Eka Ayu Nur; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The wood export industry requires strict quality standards, as even minor defects can reduce product value. PT XYZ still records defect levels above 10% tolerance, indicating that its quality control system needs improvement. This study aims to identify the root causes of defects and propose corrective actions to reduce their occurrence. Statistical Process Control (SPC) is used to determine dominant defect types, while Failure Mode and Effect Analysis (FMEA) prioritizes risks based on RPN values. The Plan Do Check Act (PDCA) cycle supported by 5W+1H serves as framework for systematic improvements. Results show that cracks, voids, improper thickness, and warping are mainly caused by unstable kiln conditions, worn moulder blades, inconsistent press pressure,and uneven wood moisture content. Implementation of PDCA actions effectively reduced finger laminating defects from 15,20-15,29% to 10,05-10,09% and decking defects from 14,62-16,66% to 10,03-10,06%. integration of SPC, FMEA, and PDCA provenly strengthens quality performance